Pressure Injury in Intensive Care Unit: prevalence and associated factors in patients with COVID-19 - Camila Mumbach de Melo; Ariane de Lourdes Gomes Bueno; Taís Loticci Rossetto; Brenda Girardi de Almeida; Liliane Becker Moretto; Marisa Basegio Carreta Diniz (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To determine the frequency of pressure injuries and identify associated risk factors in patients affected by COVID-19 admitted to an intensive care unit. Method: Cross-sectional, retrospective study with a quantitative approach carried using a documentary research. The sample included 393 medical records that were in accordance with our inclusion criteria, selected from March 2020 to March 2021 in a hospital in the south of Brazil. Data were analyzed using descriptive statistics in the software Bioestat 5. Results: The prevalence of pressure injuries in COVID-19 patients was 42%, the risk factors associated with these injuries were hospitalization time, ventilation treatment, and staying in the prone position, all with a significance of p<0.05. Conclusion: Patients with COVID-19 are subject to several unmodifiable factors that are determinant for the appearance of pressure injuries. Therefore, preventive measures should be rigorously applied to this population.